2022
DOI: 10.3390/ijms23105692
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Human Sputum for the Diagnosis of Lung Disorders: Where Are We Today?

Abstract: The identification of markers of inflammatory activity at the early stages of pulmonary diseases which share common characteristics that prevent their clear differentiation is of great significance to avoid misdiagnosis, and to understand the intrinsic molecular mechanism of the disorder. The combination of electrophoretic/chromatographic methods with mass spectrometry is currently a promising approach for the identification of candidate biomarkers of a disease. Since the fluid phase of sputum is a rich source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 101 publications
0
16
0
Order By: Relevance
“…The information of sputum in normal and disease state could be so vast that it may be considered the barometer of health. Studies of proteins in sputum have been carried out by several laboratories and more than 600 proteins found in sputum can be considered possible biomarkers of diseases [59][60][61][62]. Detection of sputum transferrin and urease has been found to be highly associated with pulmonary tuberculosis infection [59].…”
Section: Discussionmentioning
confidence: 99%
“…The information of sputum in normal and disease state could be so vast that it may be considered the barometer of health. Studies of proteins in sputum have been carried out by several laboratories and more than 600 proteins found in sputum can be considered possible biomarkers of diseases [59][60][61][62]. Detection of sputum transferrin and urease has been found to be highly associated with pulmonary tuberculosis infection [59].…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is expressed by activated macrophages and neutrophils, and it has been reported that its concentration in sputum increases up to fourfold during AE compared with that of healthy individuals . MPO is also released by neutrophils, producing hypochlorous acid bactericide . The device presented here not only detects the presence of MPO in sputum samples but also electrochemically measures the MPO activity using an appropriate redox mediator.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, proteomic analysis of sputum has gained increasing attention in the study of COPD. 77 In a recent pilot study, Dasgupta et al 55 explored the profile of sputum proteins in asthma, COPD, and chronic bronchitis. Eight proteins (Azurocidin1, Neutrophil defensin 3, Lactotransferrin, Calmodulin 3, Coronin1A, Mucin 5B, Mucin 5AC and BPI fold containing family B1) which could differentiate between exacerbation prone and nonexacerbators were identified.…”
Section: Sputummentioning
confidence: 99%